Complexity and Rights of Nature - Arce Rojas, Rodrigo (2023)
This reflective article deals with complexity and the Rights of Nature. It seeks to answer the question: How does complexity contribute to the sustenance of the Rights of Nature? For this purpose, a specialized bibliographic search was carried out. From the research it is concluded that complex thinking and the Sciences of Complexity, by being more open to epistemological and ontological diversity, by taking into account the close interrelation, interdependence and co-dependence between human beings and Nature, by highlighting from organicism the living character of the planet in cosmic relation, offer solid arguments that support the Rights of Nature. Although the Rights of Nature imply legal protection, with the State as guarantor of rights, the issue goes beyond this because what is at stake is the recognition of the intrinsic value of life in all its manifestations, beyond even sentience. It is simply the recognition of the community of life to which we all belong, and therefore we demand conviviality, respect and reciprocity.